EVALUASI PROGRAM PROMOSI DI PT. ARAS HIJRAH HOLIDAYS PEKANBARU - Anita Carolina; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
PT. Aras Hijrah Holidays is a travel agency in Pekanbaru. The booking system in PT. Aras Hijrah Holidays is still conventional. Customers are expected to come directly to the agency. In promoting their service, they use less effective media, so that the information given are not optimum. Many customers do not know the specific purpose and the price of each package offered. To overcome the existing problems, and in the increasingly sophisticated technology it is important to evaluate promotional programs in PT. Aras Hijrah Holidays through online media and adversiting media to help in expanding promotion and enhancing the company profits.This study used a qualitative method with descriptive approach, subjects of this study is President Director, Employees, and customers PT. Aras Hijrah Holidays. The data is collected by a study of documents, observation, interview, documentation.The result showed that the promotion program in PT. Aras Hijrah still konvensional can be seen from direct contact promotion program then, need Evaluation of Promotional programs is very helpful in promoting the supply of service.Keywords : Evaluation, Promotional, programs